2021
DOI: 10.1186/s12893-021-01390-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional benefits of the double flap technique after proximal gastrectomy for gastric cancer

Abstract: Background Proximal gastrectomy is a widely performed procedure that has become more common with an increasing number of proximal gastric cancer cases. Several types of reconstructive procedures after proximal gastrectomy have been developed, and it remains controversial which procedure is the most advantageous with regard to the preservation of postoperative gastric stump function and nutritional status. In the present study, we retrospectively analyzed reconstructive procedures in a consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…This structure is similar to the "reconstructed cardia" structure, which can improve the antireflux effect. Saze Z et al (16) found that the double-flap technique did not result in postoperative reflux esophagitis and had the smallest postoperative weight change ratio and the lowest prevalence of gastric residual at 12 months after surgery compared with direct esophagogastrostomy, jejunostomy and double tract reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This structure is similar to the "reconstructed cardia" structure, which can improve the antireflux effect. Saze Z et al (16) found that the double-flap technique did not result in postoperative reflux esophagitis and had the smallest postoperative weight change ratio and the lowest prevalence of gastric residual at 12 months after surgery compared with direct esophagogastrostomy, jejunostomy and double tract reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…By comparing patients who underwent direct esophagogastrostomy, jejunal interposition, double tract reconstruction, and the double-flap technique, Shoji Y ( 15 ) and Saze Z et al. ( 16 ) found that patients undergoing double-flap anastomosis had no reflux esophagitis and a lower incidence of postoperative anastomotic stricture, which improved postoperative serum albumin ratio changes and weight maintenance. Consequently, the double-flap technique is considered to be the most effective technique for proximal gastric reconstruction ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advantages: This is the first prospective large sample multicenter RCT to systematically compare the efficacy of three reconstruction methods of the digestive tract (Kamikawa versus DTR versus tube-like stomach) after proximal gastrectomy. Previous studies were mostly retrospective studies ( 25 27 ). A few prospective studies focused only on comparing the two reconstruction methods ( 28 , 29 ).…”
Section: Advantages and Limitations Of This Studymentioning
confidence: 99%
“…In conclusion, both DTR and DFT appear to be safe, feasible, and effective anti-reflux reconstruction methods after PG; however, it remains unclear which method is safer and provides better nutritional and symptomatic outcomes. Although several studies have compared DFT and DTR and reported that DFT is nutritionally superior (50)(51)(52), all of these were single-center retrospective studies. In addition, because of the most of these reports are from Eastern countries, whether these techniques are safe and effective for Western patients is unknown.…”
Section: Dtrmentioning
confidence: 99%